Vitamin E Supplementation and Its Impact on Pulmonary Tuberculosis Treatment Outcomes: A Systematic Review - Adhelia Zalsabilah Basir; Edward Pandu Wiriansya; Suciati Damopolii; Hasan Hasan; Indah Lestari Daeng Kanang (Journal La Medihealtico, 2025)
Pulmonary tuberculosis remains a global health problem, and antioxidant deficiencies such as vitamin E contribute to increased oxidative stress in patients. The aim of this study was to assess the effect of vitamin E supplementation on the effectiveness of pulmonary tuberculosis treatment through a systematic review based on PRISMA 2020 guidelines. This systematic review included clinical and observational studies investigating the relationship between vitamin E and pulmonary tuberculosis. Literature searches were conducted in PubMed and Google Scholar (2008–2021) using the keywords “Vitamin E,” “Tuberculosis,” and “Lung.” Methodological quality was assessed using the JBI Checklist and Cochrane RoB2. The process was carried out at the Faculty of Medicine, Muslim University of Indonesia, Makassar, from March to August 2024. Secondary data from published studies were used; therefore, ethical approval was not required. Six studies met the inclusion criteria, consisting of two randomized controlled trials, two in vitro studies, one case–control study, and one cross-sectional study. The synthesis results showed that vitamin E supplementation consistently reduced oxidative stress, as indicated by a significant decrease in malondialdehyde (MDA) levels and an increase in enzyme activity. In addition, vitamin E improved inflammatory status through reduced C-reactive protein (CRP) levels and increased serum leptin, as well as enhanced cellular immune responses through elevated IL-2 and IFN-γ levels. Overall, vitamin E supplementation contributed to improved treatment effectiveness and quality of life in patients with pulmonary tuberculosis.Vitamin E supplementation has potential as an adjuvant therapy that enhances the effectiveness of pulmonary tuberculosis treatment through antioxidant and immunomodulatory mechanisms.